2017
DOI: 10.3390/ijms18112393
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Reorganization of the Cytoskeleton during Apoptosis: The Two Coffins Hypothesis

Abstract: During apoptosis, cells undergo characteristic morphological changes in which the cytoskeleton plays an active role. The cytoskeleton rearrangements have been mainly attributed to actinomyosin ring contraction, while microtubule and intermediate filaments are depolymerized at early stages of apoptosis. However, recent results have shown that microtubules are reorganized during the execution phase of apoptosis forming an apoptotic microtubule network (AMN). Evidence suggests that AMN is required to maintain pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 85 publications
0
64
0
Order By: Relevance
“…Cell apoptosis, also known as programmed cell death, is a highly autonomic process that involves biochemical reactions and changes in cell characteristics [47]. Changes in early apoptotic morphology include cell shrinkage, cell membrane blebbing and chromosome concentration, and late apoptosis is characterized by the formation of apoptotic bodies and DNA fragmentation [48,49]. Similarly, we observed that a part of PM 2.5 -treated cells displayed apoptotic morphological changes in their nuclei, including formation of chromatin condensation and apoptotic bodies ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cell apoptosis, also known as programmed cell death, is a highly autonomic process that involves biochemical reactions and changes in cell characteristics [47]. Changes in early apoptotic morphology include cell shrinkage, cell membrane blebbing and chromosome concentration, and late apoptosis is characterized by the formation of apoptotic bodies and DNA fragmentation [48,49]. Similarly, we observed that a part of PM 2.5 -treated cells displayed apoptotic morphological changes in their nuclei, including formation of chromatin condensation and apoptotic bodies ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such discrepancies might occur due to different molecular mechanisms of collagen production and formation of α‐SMA–positive fibers, even though both features usually appear together in emerging fibrosis. Neither type I collagen nor α‐SMA are direct predicted targets of miR‐125b; therefore, we assume that reduced formation of α‐SMA–positive fibers may be a result of cytoskeleton reorganization due to cells entering a proapoptotic status , which is discussed below. Thus, while previously identified differentially expressed miRs in SSc promote fibrosis, in this study we demonstrated a novel role of microRNAs in the pathophysiology of SSc: the down‐regulation of miR‐125b in SSc exerts protective counterregulatory effects on the progression of skin fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐(re)organization, i. e. spatiotemporal ordering is a common phenomenon observed in nature . Cytoskeletal elements, organelles and cells undergo reorganization into different sizes, shapes and composition during the phases of cell division and this reconfiguration facilitates the various functional processes . Nature accomplishes this spatiotemporal control by dissipative self‐assembly .…”
Section: Methodsmentioning
confidence: 99%